Enhancing English vocabulary skills through storybooks at Kartini elementary school, Medan - Andi Nadira Mutia; Misla Geubrina (International Journal Linguistics of Sumatra and Malay, 2026)
This research aims to investigate the use of storybooks to enhance English vocabulary skills among young EFL learners at SD Kartini Medan (Kartini Elementary School, Medan). The research involved three different grade levels: grade 3, grade 4, and grade 5. This research focused on how storybooks support vocabulary recognition, retention, and usage. In examining this study, the researcher employed Krashen's (1982) theory on the use of additional media in learning a foreign language, namely English, and Nation's (2001) theory as a reference for providing repeated exposure to media to increase English language acquisition. The research employed a qualitative descriptive method, combining pre-test and post-test assessments with classroom observations during the treatment process. A total of 25 students participated in both the pre- and post-test phases. The results indicated that storybooks significantly improved students’ vocabulary scores and engagement, with percentage increases in class 3 (20.76%), class 4 (7.79%), and class 5 (21.88%). Story illustrations and contextual repetition helped lower-grade students grasp new words effectively, while guided reading and retelling activities supported upper-grade students in applying vocabulary in context. Although challenges such as language limitations and reliance on translation were observed, the overall findings support integrating storybooks into EFL vocabulary instruction at the elementary level.